Research case study of the Discovery Museum and Tyne & Wear Archives in Newcastle-Upon-Tyne (United Kingdom). - Yann Hui; Michael Y. Mak (Research Square, 2024)
Abstract The Discovery Museum [(built in 1899, Grade II listed) (Science & Technology Museum category)] underwent a major renovation (2004 completion), with the addition of the Tyne & Wear Archives (2008 completion) situated within the museum’s basement level. The Discovery Museum and the Tyne & Wear Archives project (Atkins, 2023) is re-visited as a research case study, via the conceptual framework lens of International Council of Museum’s (ICOM) & Organisation for Economic Co-operation & Development’s (OECD) “Culture and Local Development: Maximising the Impact (ICOM & OECD, 2019)” guide for local governments, communities and museums and the “Management of Archive & Museum Collections” lecture series (Alici, 2023). The research paper seeks to question the functional and social role of the museum within society and it’s constantly evolving identity and image, for example Cole’s vision of “museums as a schoolroom for everyone” (Hallemann, 2019). A new metaphor for the Discovery Museum’s near future vision [post COVID-19 pandemic era] will be provided within the conclusion of the paper.
Keywords: Cultural Industries and Urban Development; Fashion and Cultural Textiles; Crafts, Textile, and Design